Deciphering the functional role of clinical mutations in ABCB1, ABCC1, and ABCG2 ABC transporters in endometrial cancer - Gupta, Aayushi; Singh, Manu Smriti; Singh, Bipin (Frontiers in Pharmacology, 2024)
ABC transporters represent a superfamily of dynamic membrane-based proteins with diverse yet common functions: utilizing ATP hydrolysis to efflux substrates across cellular membranes. Three major transporters -P-glycoprotein (P-gp or ABCB1), Multidrug Resistance Protein 1 (MRP1 or ABCC1), and Breast cancer resistance protein (BCRP or ABCG2) are notoriously involved in therapy resistance in cancer patients.Despite exhaustive individual characterizations of each of these transporters, there is a lack of understanding in terms of the functional role of mutations in substrate binding and efflux, leading to drug resistance. We analyzed clinical variations reported in endometrial cancers for these transporters. For ABCB1, the majority of key mutations were present in the membrane-facing region followed by the drug transport channel and ATP-binding regions. Similarly, in ABCG2 majority of key mutations were located in the membrane-facing region followed by the ATP binding region and drug transport channel. Thus, highlighting the importance of membrane-mediated drug recruitment and efflux in ABCB1 and ABCG2. On the other hand, for ABCC1 majority of key mutations were present in the inactive nucleotide-binding domain followed by drug transport channel and membrane-facing regions, highlighting the importance of inactive nucleotide-binding domain in facilitating indirect drug efflux in ABCC1. The identified key mutations in endometrial cancer and mapped common mutations present across different types of cancers in ABCB1, ABCC1, and ABCG2 will facilitate the design and discovery of inhibitors targeting unexplored structural regions of these transporters and reengineering these transporters to tackle chemoresistance.